Musculoskeletal manifestations as determinants of quality of life impairment in patients with systemic lupus erythematosus. (February 2018) - Piga, M; Congia, M; Gabba, A; Figus, F; Floris, A; Mathieu, A; Cauli, A
Objective: The objective of this study was to identify determinants of health-related quality of life (HRQoL) impairment in patients with systemic lupus erythematosus (SLE). Methods: Overall, 101 SLE patients were recruited; 37 healthy subjects and 35 rheumatoid arthritis (RA) patients served as controls. HRQoL was evaluated using three patient reported outcomes (PROs): the Short Form-36 version 2 (SF-36v2) health survey, the fatigue scale version 4 (FACITv4) and the Heath Assessment Questionnaire (HAQ). A large set of demographic and clinical variables, including SLE arthritis subtypes, was evaluated searching for factors independently associated with worse QoL. Multivariate models were applied to identify factors independently associated with outcomes. Bonferroni's corrected p values < 0.05 were considered significant. Results: SLE patients showed worse results than healthy controls ( p < 0.01) in all SF-36v2 domains and, with reference to the mental QoL, also than RA patients ( p < 0.01). Jaccoud's deformities, active arthritis, and fibromyalgia were the only factors independently associated with worse results in both physical and mental components summary of the SF-36v2 ( p < 0.01) and FACITv4 fatigue scale ( p < 0.01). Fragility fractures, deformities, and active arthritis negatively affected disability perception measured by the HAQ ( p < 0.01). No statistically significant differences in perceived HRQoL were highlighted between patients with deforming and erosive arthritis. However, they had significantly worse results than patients with non-deforming non-erosive arthritis across all investigated PROs ( p < 0.01). Conclusion: In order to limit musculoskeletal manifestations as a source of impaired QoL in SLE patients, therapeutic strategies targeted to successfully manage active arthritis and fibromyalgia and to prevent deforming damage are needed.